Commensuration of the globalised higher education sector: how university rankings act as a credential for world-class status in China. Issue 6 (18th August 2021) - Allen, Ryan M.
ABSTRACT: The concept of the world-class university has proliferated throughout the world, yet there is no universal consensus on how to define these elite institutions. Without a unified definition, rankings have become a direct proxy for sense-making in the sector and a commensurate indicator that decision-makers have used to understand the world-class concept. Through interviews with 48 informants from the Chinese higher education sector, I explore how institutions in China conceptualise world-class status through university rankings. First, I show that the sector in China has intently focused on league table positioning, with the top-100 as a popular cut-off point for guaranteed world-class status. Next, I explore which global rankings have been the most influential – QS, THE, ARWU, and US News . Finally, I discuss how actors living in this competitive higher education environment have altered research agendas and institutional partnerships to align with global ranking metrics.